Plan de bienestar laboral para la Empresa Inversiones García Forero S.A.S. (2021)
At present, labor well-being is a fundamental factor in the development of human talent in SMEs or MSMEs at the national and international level, which is why the present work aims to analyze the current situation of the company Inversiones García Forero SAS in front of to its human management area in order to initiate a proposal for labor welfare, which will be developed against the information collected.